Yes, nós temos arquitetura moderna! Reconstituição e análise da arquitetura residencial moderna em Natal das décadas de 50 e 60 - Melo, Alexandra Consulin Seabra de (2004)
Brazilian architecture was recognized because of the consecration of the icons of the Carioca and Paulista schools which are represented nationally and internationally by names like Niemeyer, Lucio Costa and Vilanova Artigas, among others. Because of this, classic studies dedicated to the Brazilian case look to present the Southeastern region with the title of father of modern Brazil, at the cost of subjugating various other modern movements and peripheral sayings, whether their values are known or forgotten. On the other hand, there has been an effort, in the sense of registering and analyzing these regional productions of modern Brazilian architecture, an assignment that DOCOMOMO Brasil participates firmly through initiatives like the creation of a Library to aid in the documentation and registration of modernity in Brazil. Inside this context of insertions of the National-Modern scheme, this work has as its objective to present modern potiguar (northern Brazil) architecture through its contemporary residential examples, investigating specifically its constructive, formal aspects, that together that together demonstrate one more architectural emphasis of modern Brazilian architecture: the potiguar. This way, by contributing to the work of the register and the documentation of the Modern Movement and attributing to the modern architecture of Natal it s real worth, we can say: Yes, we have modern architecture